Working with Randolph-Sheppard Entrepreneurs who Are Deafblind: A Qualitative Analysis. (January 2017) - Hierholzer, Anne C.; Bybee, Jacquelyn
Introduction: The purpose of the study was to explore challenges facing deafblind entrepreneurs and the staff who work with them through the Randolph-Sheppard Business Enterprise Program. Methods: Interviews were conducted with 41 Randolph-Sheppard staff and deafblind entrepreneurs across the United States. Participants were selected using a snowball sampling procedure. Interviews were conducted by telephone or e-mail, and results were coded to identify overarching themes. Results: The top challenge identified among all staff was helping deafblind entrepreneurs interact effectively with customers. Common communication challenges included reliance on third parties and communication that was characterized by repetition and slowness. Although challenges surrounding communication were commonly cited by staff, problems with technology were the most important concerns for the entrepreneurs themselves. Over one-third of respondents (36%) felt deafblindness did not create any unique communication challenges. Common suggestions for program improvement were expanding access to interpreters and training in sign language and tactile interpreting. Discussion: Entrepreneurs and staff agreed that many challenges relating to deaf-blindness can be overcome with creativity and determination. One important approach for improving communication is proactively informing customers about the entrepreneur's deafblindness and describing communication strategies. Further research to determine the extent of hearing loss among entrepreneurs in the Randolph-Sheppard program would be beneficial. Implications for practitioners: Individuals with deafblindness have demonstrated the ability to take part in the workplace, but challenges remain. Staff who work with these entrepreneurs need to help them address their unique communication needs in a proactive, positive manner.